Koncepcija razvitija licnostno orientirovannoj sistemy fiziceskoj kul'tury i sporta v Leningradskoj oblasti - Vazenin, S. A. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The author submits for consideration his own concept of the individual focused physical culture and sports. it allows optimally to combine interests of professional work and of a concrete person by means of its familiarizing with the process of physical perfection at different age stages of the individual physical development.